Extracellular Vesicle-Enhanced Stem Cell Therapy in Acute Myocardial Infarction: A Case Report of Cardiac Regeneration from a Bypass Surgery - Halil Hüzmeli; Ayberk Akat; Ahmet Özkara; Emel Ceylan; Ebru Özenç; Erdal Karaöz (Stem Cell Reviews and Reports, 2025)
Myocardial infarction is still a significant cause of morbidity and mortality. Coronary artery obstruction reduces blood flow and oxygen supply to the heart muscle, resulting in ischemia and necrosis. Due to the heart's limited healing mechanisms, regenerative therapies to restore cardiac function are being investigated. This case report, describes the utilization of mesenchymal stem cells and extracellular vesicles derived from these cells during coronary artery bypass grafting surgery for the patient who had a recent acute myocardial infarction. A direct injection into the myocardium was performed during surgery after a failed percutaneous coronary intervention. During the follow-up, the patient demonstrated improvements in cardiac function, with the ejection fraction increasing from 28 to 35% as measured by myocardial perfusion scintigraphy, and up to 43% on echocardiographic assessment at six months post-operation, as well as decreases in end-diastolic and end-systolic volumes. Significantly, these advantages remained despite the blockage of the bypass graft. The present case shows that extracellular vesicle-enhanced stem cell treatment may be used in surgical revascularization to restore myocardium in severe ischemic damage. Graphical Abstract